2016
DOI: 10.3390/nu8060336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immune-Enhancing Enteral Nutrition Enriched with or without Beta-Glucan on Immunomodulation in Critically Ill Patients

Abstract: We investigated whether high-protein enteral nutrition with immune-modulating nutrients (IMHP) enriched with β-glucan stimulates immune function in critically ill patients. In a randomized double-blind placebo-controlled study, 30 patients consumed one of three types of enteral nutrition: a control or IMHP with and without β-glucan. The IMHP with β-glucan group showed increases in natural killer (NK) cell activities relative to the baseline, and greater increases were observed in NK cell activities relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A randomized double-blind placebo-controlled study on 30 critically ill ICU patients, followed for 7 days, found significant increases in NK cell activities when given immune-enhancing enteral nutrition (IMHP) enriched with ß-glucan from the baseline and significantly greater increase than the control group [ 41 ]. The authors suggest that ß-glucan can be an attractive candidate to add to IMPH for stimulation of protective immunity without enhanced inflammation in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized double-blind placebo-controlled study on 30 critically ill ICU patients, followed for 7 days, found significant increases in NK cell activities when given immune-enhancing enteral nutrition (IMHP) enriched with ß-glucan from the baseline and significantly greater increase than the control group [ 41 ]. The authors suggest that ß-glucan can be an attractive candidate to add to IMPH for stimulation of protective immunity without enhanced inflammation in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric parameters, serum lipid profiles, glucose, nutritional status, liver and renal function tests, cytokine levels in serum and PBMC supernatants, and NK cell activity were analyzed as previously described [ 25 ]. Detailed information about assessments of cytokine levels in serum and PBMC supernatants, and NK cell activity were described in supplementary information (See Additional File 1).…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al studied the immunomodulating effects of nutrients enriched with β-glucans in critically ill patients with pulmonary disease and trauma [ 160 ]. In a randomized, double-blind, placebo-controlled study, β-glucan-enriched fractions showed an increase in natural killer cell activities and serum albumin.…”
Section: Immunomodulating Effects Of β-Glucansmentioning
confidence: 99%